Hubungan derajat dehidrasi dengan kadar hematokrit pada anak penderita diare di RSUP Prof. Dr. R. D. Kandou Manado - Rumayar, Angely C.; Manoppo, Jeanette I.Ch.; Mantik, Max F.J. (e-CliniC, 2016)
Abstract: The most severe threat that can inflicted by diarrhea is dehydration. In dehydration patients, hematocrit levels can increase. This study was aimed to find out the relationship between degree of dehydration and hematocrit level among diarrhea children at Prof. Dr. R. D. Kandou Manado hospital.This was an observational analytical study. Data were obtained from the medical record of pediatric patients retrospectively and were analyzed with the chi square test. The results showed that there were 40 pediatric patients with diarrhea. Most were females (57.5%), and the average age was 8.5 years. Increased hematocrit level in diarrhea cases without dehydration was more dominant than in diarrhea cases with dehydration. The chi square test showed a p value of 0.949. Conclusion: There was no significant relationship between degree of dehydration and hematocrit level.Keywords: diarrhea, children, degree of dehydration, hematocrit levelÂ Abstrak: Ancaman paling parah yang ditimbulkan oleh diare ialah dehidrasi. Dalam keadaan dehidrasi kadar hematokrit penderita dapat meningkat. Penelitian ini bertujuan untuk mengetahui hubungan derajat dehidrasi dengan kadar hematokrit pada anak penderita diare di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah analitik observasional dengan pendekatan retrospektif. Data diperoleh dari rekam medik pasien anak di RSUP Prof. Dr. R. D. Kandou Manado dan dianalisis dengan uji chi square. Hasil penelitian mendapatkan 40 pasien anak dengan diare, terbanyak pada perempuan (57,5%), usia rata-rata 8,5 tahun, Peningkatan kadar hematokrit pada kasus diare tanpa dehidrasi lebih banyak dibandingkan kasus diare dengan dehidrasi. Hasil uji chi square menunjukkan nilai p = 0,494. Simpulan: Tidak terdapat hubungan bermakna antara derajat dehidrasi dengan kadar hematokrit. Kata kunci: diare, anak, derajat dehidrasi, kadar hematokrit